2021
DOI: 10.3390/app11209779
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Task Complexity on Time Estimation in the Virtual Reality Environment: An EEG Study

Abstract: This paper investigated the effect of task complexity on time estimation in the virtual reality environment (VRE) using behavioral, subjective, and physiological measurements. Virtual reality (VR) is not a perfect copy of the real world, and individuals perceive time duration differently in the VRE than they do in reality. Though many researchers have found a connection between task complexity and time estimation under non-VR conditions, the influence of task complexity on time estimation in the VRE is yet unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 78 publications
(122 reference statements)
1
4
0
Order By: Relevance
“…As a result, the estimation error was greater in the virtual situation, and the participants considered (with regard to the results of the NASA-TLX questionnaire) that the mental load associated with estimating distances in the virtual situation to be greater than that associated with the same task in the real situation. These results are consistent with the literature, showing that a higher mental workload is associated with greater task complexity [ 31 , 32 , 33 , 34 ] and that a high mental workload is generally associated with a decrease in performance [ 35 ]. In our study, the decrease in performance corresponded to an increase in the distance estimation error in a virtual situation.…”
Section: Discussionsupporting
confidence: 92%
“…As a result, the estimation error was greater in the virtual situation, and the participants considered (with regard to the results of the NASA-TLX questionnaire) that the mental load associated with estimating distances in the virtual situation to be greater than that associated with the same task in the real situation. These results are consistent with the literature, showing that a higher mental workload is associated with greater task complexity [ 31 , 32 , 33 , 34 ] and that a high mental workload is generally associated with a decrease in performance [ 35 ]. In our study, the decrease in performance corresponded to an increase in the distance estimation error in a virtual situation.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, betaband activation has also been linked with perception of time across multiple studies (e.g., Ghaderi et al, 2018;Damsma et al, 2021). The work by Li and Kim (2021) also showed that beta band activity around the Fpz region could be linked to task complexity, which in turn, was shown to also modulate time perception. In a similar vein, the work by Wiener et al (2018) showed that transcranial alternating current stimulation over the fronto-central cortex at beta frequency could shift the perception of time to make stimuli seem longer in duration.…”
Section: Feature Importancementioning
confidence: 97%
“…d) Flicker rate and duration, the frequency and duration of the blinks of the eyes decrease with MWL [37] decrease fixation duration, the fixation is shorter when MWL is present [35]. e) Pupil dilatation, the eye pupil gets bigger with MWL [38,39,40]. f) Intraocular pressure (IOP) high values are related to high MWL values [41,42].…”
Section: Physiological Mwl Measurementsmentioning
confidence: 99%